Clinical outcomes after final kissing balloon inflation compared with no final kissing balloon inflation in bifurcation lesions treated with a dedicated coronary bifurcation stent. Issue 6 (15th January 2014) - Grundeken, Maik J; Lesiak, Maciej; Asgedom, Solomon; Garcia, Eulogio; Bethencourt, Armando; Norell, Michael S; Damman, Peter; Woudstra, Pier; Koch, Karel T; Vis, M Marije; Henriques, Jose P; Tijssen, Jan G; et al.
Abstract : Objective: We evaluated differences in clinical outcomes between patients who underwent final kissing balloon inflation (FKBI) and patients who did not undergo FKBI in bifurcation treatment using the Tryton Side Branch Stent (Tryton Medical, Durham, North Carolina, USA). Methods: Clinical outcomes were defined as target vessel failure (composite of cardiac death, any myocardial infarction and clinically indicated target vessel revascularisation), cardiac death, myocardial infarction (MI), clinically indicated target vessel revascularisation and stent thrombosis. Cumulative event rates were estimated using the Kaplan-Meier method. A multivariable logistic regression analysis was performed to evaluate which factors were potentially associated with FKBI performance. Results: Follow-up data was available in 717 (96%) patients with a median follow-up of 190 days. Cardiac death at 1 year occurred more often in the no-FKBI group (1.7% vs 4.6%, respectively, p=0.017), although this difference was no longer observed after excluding patients presenting with ST segment elevation MI (1.6% vs 3.3%, p=0.133). No significant differences were observed concerning the other clinical outcomes. One-year target vessel failure rates were 10.1% in the no-FKBI group and 9.2% in the FKBI group (p=0.257). Multivariable logistic regression analysis identified renal dysfunction, ST segment elevation MI as percutaneous coronary intervention indication, narrow (<30°) bifurcation angle and certain stent platforms as being independently associated with unsuccessful FKBI. Conclusions: A lower cardiac death rate was observed in patients in whom FKBI was performed compared with a selection of patients in whom FKBI could not be performed, probably explained by an unbalance in the baseline risk profile of the patients. No differences were observed regarding the other clinical outcomes.